The Effect of Emotional Labor and Depression on the Quality of Life of Call Center Workers (Cuestiones de Fisioterapia, 2024)
Purpose: The purpose of this study is to examine the impact of emotional labor and depression among call center workers on their quality of life. Methods: The survey was conducted from March 28th to April 8th, 2023, and the study participants were 170 call center workers from K Telecommunications located in S city in South Korea. Descriptive statistical analysis was used to examine the general characteristics of the participants. Differences in emotional labor, depression, and quality of life based on the participants' general characteristics were analyzed using t-tests and ANOVA. The correlation between emotional labor, depression, and quality of life was examined using Pearson's correlation coefficient analysis. Factors influencing quality of life were determined using multiple regression analysis. Results: According to the research findings, there was a significant negative correlation between quality of life and emotional labor (r=-.35, p<.001) as well as depression (r=-.53, p<.001). Factors influencing the participants' quality of life were identified as emotional labor (t=-.08, p=.003), depression (t=-7.93, p<.001), cohabiting family (t=.77, p=.030), and average monthly income (t=1.31, p=.010) (F=17.15, p<.001). Conclusions: Therefore, in order to enhance the quality of life for call center workers, it is necessary for workplaces to implement management measures addressing emotional labor and depression. Furthermore, concerted efforts and agreements between labor and management are required to improve social support for workers and enhance working conditions.